2019
DOI: 10.29328/journal.cjog.1001027
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate in management of Morbidly Adherent Placenta at Latifa Hospital, DHA, Dubai, UAE.: Case report

Abstract: The surgical management choices may be considered according to available expertise, geographical and individual circumstances. Conservative approaches for women who wish to preserve their fertility aim to avoid hysterectomy. Some conservative treatments for uterus preservation include expectant management (wait and see), uterine artery embolization, Methotrexate therapy and uterus preserving surgeries (such as uterine internal/iliac artery ligation and balloon tamponade) [2]. Methotrexate has been used for man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, there are some success stories (spontaneous placental expulsion and faster complete involution) reported from the case series studies with methotrexate administration (67)(68)(69). A recent published study from China (including 54 cases for expectant management) has reported a success rate of 92.5% by administering methotrexate intravenously or local multi-point injection under ultrasound guidance, with 100% success in the latter group (61).…”
Section: Commentmentioning
confidence: 99%
“…However, there are some success stories (spontaneous placental expulsion and faster complete involution) reported from the case series studies with methotrexate administration (67)(68)(69). A recent published study from China (including 54 cases for expectant management) has reported a success rate of 92.5% by administering methotrexate intravenously or local multi-point injection under ultrasound guidance, with 100% success in the latter group (61).…”
Section: Commentmentioning
confidence: 99%